2021
DOI: 10.1177/08968608211004683
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor-mediated peritoneal neoangiogenesis in peritoneal dialysis

Abstract: Peritoneal dialysis (PD) is an important renal replacement therapy for patients with end-stage renal diseases, which is limited by peritoneal neoangiogenesis leading to ultrafiltration failure (UFF). Vascular endothelial growth factor (VEGF) and its receptors are key angiogenic factors involved in almost every step of peritoneal neoangiogenesis. Impaired mesothelial cells are the major sources of VEGF in the peritoneum. The expression of VEGF will be up-regulated in specific pathological conditions in PD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 157 publications
(228 reference statements)
0
18
0
Order By: Relevance
“…Among all molecules that regulate peritoneal angiogenesis, VEGF as a strong pro-angiogenic factor binds to VEGFR expressed on the cell surface of vascular endothelial cells, stimulating the formation of new capillaries in the peritoneal membrane. Increased effective vascular surface area accelerates glucose uptake from the dialysate into the circulation, leading to a dissipation of glucose-driven osmotic pressure, which ultimately results in ultrafiltration failure (UF) (Aroeira et al, 2005;Saxena, 2008;de Lima et al, 2013;Shi et al, 2022). The selective high expression of endoglin on tumour vessels has led to widespread attention to it as a target for cancer therapy, reminding us whether anti-endoglin treatment could similarly improve peritoneal angiogenesis and thus reduce PF (Paauwe et al, 2016;Kasprzak and Adamek, 2018;Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Among all molecules that regulate peritoneal angiogenesis, VEGF as a strong pro-angiogenic factor binds to VEGFR expressed on the cell surface of vascular endothelial cells, stimulating the formation of new capillaries in the peritoneal membrane. Increased effective vascular surface area accelerates glucose uptake from the dialysate into the circulation, leading to a dissipation of glucose-driven osmotic pressure, which ultimately results in ultrafiltration failure (UF) (Aroeira et al, 2005;Saxena, 2008;de Lima et al, 2013;Shi et al, 2022). The selective high expression of endoglin on tumour vessels has led to widespread attention to it as a target for cancer therapy, reminding us whether anti-endoglin treatment could similarly improve peritoneal angiogenesis and thus reduce PF (Paauwe et al, 2016;Kasprzak and Adamek, 2018;Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the density of peritoneal microvessels predicts glucose transport independent of other factors (25). On the molecular level, VEGF is the best characterized mediator of angiogenesis (28) and it plays a role in peritoneal membrane dysfunction in PD (17,29,30). Prior studies identified the mesothelium as an important source of VEGF in the peritoneum and deciphered pathways of VEGF induction during PD (16,17,(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a review newly published by our team systematically summarizes the angiogenic effect of VEGF. VEGF is associated with high peritoneal transport rate while impaired mesothelial cells are the major sources of VEGF in the peritoneum 30 …”
Section: Introductionmentioning
confidence: 99%
“…VEGF is associated with high peritoneal transport rate while impaired mesothelial cells are the major sources of VEGF in the peritoneum. 30 Since the evaluation of peritoneal function of patients is after the start of peritoneal dialysis, there are still a large number of patients with initial high PSTR who undergo PD and their prognosis is not clear. This study was undertaken to evaluate the subsequent overall survival and technique survival of the PD patients grouped by their baseline peritoneal transport status, analyse independent predictive risk factors of high baseline peritoneal transport status and explore its potential pathogenesis through in vitro experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation